ANALISIS EFEKTIVITAS PENGELOLAAN DANA DESA (DD) DALAM PENINGKATAN PEMBANGUNAN FISIK DESA TAWANG KECAMATAN SUSUKAN KABUPATEN SEMARANG - Handayani, Titik; Hegy Suryana, Alean Kistiani; Triatmaja, Nur Asih; Markhumah, Umatun; Shukor Harun , Mohd (Universitas Boyolali, 2025)
The purpose of this study was to analyze the effectiveness of village fund management in increasing the physical development of Tawang Village. The method used in this research is descriptive with a quantitative approach. Data obtained through observation, interviews and documentation. The data processed is sourced from the APBDesa and Tawang Village APBDes Realization Report relating to physical development for the 2019-2022 period. The calculation technique used is the effectiveness ratio. The results of the study show that the management of village funds in increasing the physical development of Tawang Village is at an effective level with the results of the effectiveness ratio in 2019 to 2022 showing 100%. Apart from that, interviews conducted with several informants also showed that the management of village funds starting from the planning, implementation, administration, reporting and accountability stages had been carried out by the government properly and there was real/physical evidence of government performance.